A Conceptual Framework on the Process of Personal Transformation in a Primary Health Care Context for Living with a Chronic Illness - Claire-Jehanne Dubouloz; Judy King; Barbara Paterson; Brenda Ashe; Jacques Chevrier; Mirela Moldoveanu (Adult Education Research Conference, 2012)
The objective of this study is to propose a conceptual framework that could explain the process of personal transformation within a Primary Health Care context for people living with chronic illnesses.